Simetry of stereograms used in the determination of the optical indicatrix of minerals - Marconi, Arary; Abrahão, Ibrahim Octavio (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
There is a simetry relation between stereograms constructed with the aid of the analytical method of determining the optical indicatrix of minerals in thin section, in the universal stage. This simetry is discussed in this paper. It is a plane-simetry which always occurs both in the ψ 1 and ψ2 graphics and curves when ψ1 + ψ2 = 90°.